High-intensity interval neuromuscular training promotes exercise behavioral regulation, adherence and weight loss in inactive obese women. Issue 6 (2nd July 2020) - Batrakoulis, Alexios; Loules, Georgios; Georgakouli, Kalliopi; Tsimeas, Panagiotis; Draganidis, Dimitrios; Chatzinikolaou, Athanasios; Papanikolaou, Konstantinos; Deli, Chariklia K.; Syrou, Niki; Comoutos, Nikolaos; Theodorakis, Yiannis; Jamurtas, Athanasios Z.; et al.
Abstract: It is unclear how high-intensity, interval-type nontraditional exercise training programmes can be feasible and effective options for inactive obese individuals. This randomized controlled trial investigated the hypothesis that a 10-month high-intensity, interval-type neuromuscular training programme (DoIT) with adjunct portable modalities, performed in a small-group setting, induces improvements in psychological well-being, subjective vitality and exercise behavioural regulations in obese women. Associations between adherence, psychological and physiological indicators were also investigated. Forty-nine previously inactive obese females (36.4 ± 4.4 yrs) were randomly assigned to three groups (control; N  = 21, 10-month training; N  = 14, or 5-month training plus 5 month-detraining; N  = 14). DoIT was a supervised, progressive, and time-efficient (<30 min) programme that used 10–12 functional/neuromotor exercises and prescribed work and rest time intervals (20–40 sec) in a circuit fashion (1–3 rounds) for 10 months. Questionnaires were used to measure psychological distress, subjective vitality, and behavioural regulations in exercise at pre-, mid-, and post-intervention. The 10-month training reduced psychological distress (72%, p  = 0.001), external regulation (75%, p  = 0.011) and increased vitality (53%, p  = 0.001), introjected regulation (63%, p  = 0.001), intrinsic regulation (33%, p  = 0.004), and identified regulation (88%, p  = 0.001). A moderate to strong positive relationship was found between adherence rate and identified regulation scores ( r  = 0.59, p  = 0.001) and between VO2 peak and identified regulation scores ( r  = 0.59, p  = 0.001). A mild dissociation between exercise intensity and perceived exertion was also observed. Our novel findings suggest that a 10-month implementation of a high-intensity interval neuromuscular training programme promotes positive psychological adaptations provoking exercise behavioural regulation and adherence while inducing weight loss in inactive obese women.